Analisis Penerapan Aplikasi Keuangan Simmona Dalam Pengelolaan Keuangan Di Kantor Keuangan FITK UIN Sumatera Utara - Sri Wahyuni Nurma Ningsih; Lailan Syafina (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the effectiveness and obstacles of implementing the SIMMONA application in financial management at the Finance Office of FITK UIN SUMATRA UTARA. This research uses a qualitative approach with a qualitative descriptive research type. The data used comes from interviews with financial operators at the FITK financial office. The research results show that the implementation of the SIMMONA application in the Finance Office of FITK UIN SUMATRA UTARA has been running effectively and efficiently in assisting Finance Employees in managing the finances of the Tarbiyah and Teacher Training Faculty of UIN SUMATRA UTARA. However, in its operation there are still obstacles that do not have a significant impact, namely the system errors while being used, which hinders the data input process and disrupts network connections. The SIMMONA application has a very important influence in the FITK Finance Office, where with this system, FITK's financial management will create optimal accountability and transparency. And the SIMMONA application can also minimize recording and calculation errors.